International Business - Stuart Wall; Sonal Minocha; Brownen Rees (Harlow, England Pearson, 2015)
We live in a global economy in which over one quarter of the world's recorded output is exported, where a change in business practice in Beijing can have a direct impact on a workforce in Birmingham, and where support to a customer in Detroit can be provided from Delhi. This book provides a clear and concise introduction to this most interdisciplinary of subjects, explaining in straightforward language the economic and financial underpinnings of international business, and the more subtle organisational and cultural issues increasingly crucial to business success. The managerial challenges which face organisations of all types and sizes, no matter where they are located, are reviewed and explored.
Keywords: International business enterprises; International economic relations; Globalization; Business; International Business and Management (ECO2023-N )